(untitled) (Journal of Geography and Environmental Management, 2024)
The article discusses spatiotemporal changes in the main climatic indicators in the period 1941-2020, their impact on the possibilities of the atmospheric self-purification of a lead-zinc mine. The study of changes in air temperature showed the presence of long-term trends, and the climatic potential parameters of the dissipative capacity of the mine atmosphere were calculated. It was found that the average monthly air temperature increases with the rate of warming of 0.19 to 0.34 °C every 10 years. Moreover, a relatively greater increase in temperature occurs in winter, and a smaller increase in summer. Determined that the anomalous air temperature field is large in the study area both in winter and summer months. Based on the calculations, data on the spatiotemporal variability of the climatic potential of the dissipation capacity and the coefficient of atmospheric self-purification were obtained. This made it possible to establish that throughout the entire annual cycle, unfavorable conditions are observed for the dispersion of polluting particles in the atmospheric air, and to a greater extent during the cold period of the year. The results indicate the manifestations of natural and anthropogenic atmospheric processes that prevent the dispersion of pollution in the atmosphere. The performed research is significant for the practical use. Since data on the spatial and temporal variability of the dispersion potential of atmospheric air must be previously assessed when implementing measures to manage air quality in an industrial region.